Nanomaterials for Cortisol Sensing - Giuseppe Trusso Sfrazzetto; Rossella Santonocito (Nanomaterials, 2022)
Space represents one of the most dangerous environments for humans, which can be affected by high stress levels. This can lead to severe physiological problems, such as headaches, gastrointestinal disorders, anxiety, hypertension, depression, and coronary heart diseases. During a stress condition, the human body produces specific hormones, such as dopamine, adrenaline, noradrenaline, and cortisol. In particular, the control of cortisol levels can be related to the stress level of an astronaut, particularly during a long-term space mission. The common analytical methods (HPLC, GC-MS) cannot be used in an extreme environment, such as a space station, due to the steric hindrance of the instruments and the absence of gravity. For these reasons, the development of smart sensing devices with a facile and fast analytical protocol can be extremely useful for space applications. This review summarizes the recent (from 2011) miniaturized sensoristic devices based on nanomaterials (gold and carbon nanoparticles, nanotubes, nanowires, nano-electrodes), which allow rapid and real-time analyses of cortisol levels in biological samples (such as saliva, urine, sweat, and plasma), to monitor the health conditions of humans under extreme stress conditions.